Invertebrates and Vertebrates Fauna of Zameer Gul Dam, Kohat, Khyber Pakhtunkhwa, Pakistan - Kalim Ullah; Aasma Momeen; Eman Khalil; Maria Bibi; Nadia Kalsoom; Ayesha Ihsan Qazi (Zien Journals, 2022)
The basic aim of the present study was to find out the vertebrates and invertebrates’ fauna of Zameer gul dam to provide useful information for future studies. During our research work, different samples of fishes were collected from the different sites of the Zameer Gull Dam Kohat with the help of local fishermen using different types of catch nets and were preserved in 10% formalin. The birds were counted by using a binocular (8x to 32x) and were identified. Observations of mammals were made using field binoculars (32x50) and all species were arranged according to their taxonomic classification. The collected samples of invertebrates were identified by using various identification keys. In our research, we discovered six fish species belonging to one class, two orders, and two families during our research. Three amphibian species were discovered, belonging to one class, one order, and three families. There were four reptile species found, with one class, four orders, and eight families. During our research, we found seven mammalian species belonging to one class, three orders, and four families. Six species of invertebrates, comprising eight wasps and five spiders, were found to belong to three classes, five orders, and six different families. From the current study it can be concluded that Zameer gull dam provide suitable environmental conditions to support the diversity of both vertebrates and invertebrates. The water of this dam is of good quality. Government should pay attention to this dam for making this dam excellent for life and irrigation.
Keywords: Invertebrates; vertebrates; diversity; Dam